Spleen Transient Elastography and Damping Index Identify a Subgroup of Patients Without an Acute or Chronic Response to Beta-Blockers - Llop, Elba; Perelló, Christie; Fontanilla, Teresa; de la Revilla, Juan; Conde, Marta Hernández; López, Marta; Minaya, Javier; Ferre, Carlos; Abad, Javier; Carrillo, Carlos Fernández; Martínez, José Luís; Puga, Natalia Fernández; et al. (Frontiers in Medicine, 2022)
Background and Aims: Monitoring of acute or chronic response to beta-blockers in patients with liver cirrhosis is based on the measurement of the HVPG. Our aim was to evaluate response to beta-blockers with non-invasive techniques. Patients and methods: Prospective observational study. Consecutive patients with indication of primary or secondary prophylaxis of variceal bleeding who did not met exclusion criteria were included. Acute response and chronic response were evaluated. Baseline and after acute and chronic response hepato-splenic measurements of TE and ARFI were obtained. Contrast enhanced doppler ultrasound was performed before and after acute and chronic response. Results: From June 2015 to May 2018, 55 patients (14 with exclusion criteria) were included. We analyzed 41 patients, mean age 57(SD8), 82.9% males, alcohol 43.9%, Child A/B/C 78%/17.1%/ 4.9% and 87.8% on primary prophylaxis. In all, acute response was performed and in 68.3% (CI 95 55%-85%) was positive. Chronic response was performed in 30(73.2%) and was positive in 36.7%(CI 95 18%-55%). Basal measurements related significantly with acute response were: spleen TE (responders 58.4(SD 23.0)KPa vs. non-responders 75(SD0)KPa; p=0.02) and damping index (non responders 0.96(0.8) vs. responders 0.44(0.4), p=0.01), and with chronic response, the spleen TE (responders 58.1(SD21.4)KPa vs. non responders 73.2(SD5.5)KPa; p=0.02) and damping index (non chronic responders 0.8(0.7) vs. chronic responders 0.4(0.4),p=0.04). A spleen TE >=74 KPa had high sensitivity 100% and specificity 60% and high NPV100% for predicting poor acute response to beta-blockers. Damping index>0.6 showed moderate sensitivity 67% and specificity 69% with high NPV 82% for predicting poor acute response to beta-blockers. The combination of both measurements for predicting poor acute response to beta-blockers had an AUC 0.8(CI 95 0.5-0.9). A spleen TE >=74KPa had high sensitivity 87% and specificity 71% with high NPV71% for predicting poor chronic response to beta-blockers. A damping index >0.6 had moderate sensitivity 60%, specificity 82% and NPV56% for predicting poor chronic response to beta-blockers. The combination of both measurements for predicting poor chronic response to beta-blockers had an AUC 0.8(CI 95 0.7-0.9). Conclusion: Spleen TE and damping index are able to identify a subgroup of patients with poor acute or chronic response to beta-blockers.